2020
DOI: 10.18332/ejm/126625
|View full text |Cite
|
Sign up to set email alerts
|

Midwives’ views towards women using mHealth and eHealth to self-monitor their pregnancy: A systematic review of the literature

Abstract: INTRODUCTION There are many mobile telephone apps to help women self-monitor aspects of pregnancy and maternal health. This literature review aims to understand midwives' perspectives on women self-monitoring their pregnancy using eHealth and mHealth, and establish gaps in research. METHODS MEDLINE, PubMed, Scopus, CINAHL and PsycINFO were systematically searched on midwifery, eHealth/mHealth and perspectives. Qualitative, quantitative and mixed-methods studies published in English were considered for inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 27 publications
3
31
0
Order By: Relevance
“…Effective weight management and return to healthy weight range was achieved by participants who adhered to online dietary advice to manage their gestational diabetes in one of the included studies [ 39 ]. These findings agreed with another review by Vickery et al [ 55 ] that found that effective utilisation of mobile and web-based health intervention promoted healthy gestational weight gain in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…Effective weight management and return to healthy weight range was achieved by participants who adhered to online dietary advice to manage their gestational diabetes in one of the included studies [ 39 ]. These findings agreed with another review by Vickery et al [ 55 ] that found that effective utilisation of mobile and web-based health intervention promoted healthy gestational weight gain in pregnancy.…”
Section: Discussionsupporting
confidence: 92%
“…This combination of passive learning with interactive tools of social networks can help PLW to improve their self-information skills, therefore healthcare professionals must be prepared to support the retrieval, interpretation and request of online information [ 1 , 47 , 65 , 66 ]. A recent systematic review aimed at understanding midwives’ perspectives on women self-monitoring of their pregnancy using eHealth concluded that they generally hold ambivalent views [ 67 ]. While noting its potential to help women to make informed decisions, they also point out the risk of accessing inaccurate information [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review aimed at understanding midwives’ perspectives on women self-monitoring of their pregnancy using eHealth concluded that they generally hold ambivalent views [ 67 ]. While noting its potential to help women to make informed decisions, they also point out the risk of accessing inaccurate information [ 67 ]. This highlights the necessity of providing PLW with specific skills to find and interpret valid and reliable health information online.…”
Section: Discussionmentioning
confidence: 99%
“…However, qualitative reviews on midwives reported unfavorable findings which did not fully support the apps for several reasons [ 24 ]. Midwives were concerned about the accuracy of the apps [ 25 ] and their negative impacts on the patient-professional relationship, such as shifting the patient’s trust from trusted to untrusted sources [ 24 ].…”
Section: Introductionmentioning
confidence: 99%